TRANSFORMING CONSCIOUSNESS THROUGH MEDITATION AND MINDFULNESS: THE PATH TO EMOTIONAL BALANCE AND MENTAL HEALTH - Zulaikah, Enik; Khamami, Akhmad Rizqon; Maftukhin, Maftukhin (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to examine how transforming consciousness through meditation and mindfulness practices can contribute to emotional balance and individual mental health. The background of this research is based on the increasing global psychological problems, such as stress, depression, anxiety, and burnout, which are widely experienced by modern society. Meditation and mindfulness are seen as alternative and complementary methods that can foster self-awareness, reduce emotional reactivity, and build inner balance. The research method used is a Systematic Literature Review (SLR) by examining international scientific articles published in the last ten years. The selection process was carried out through searches in indexed databases such as Scopus, Web of Science, and Google Scholar with the keywords